2016
DOI: 10.1136/heartjnl-2015-308559
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia in ST elevation myocardial infarction: a systematic review and meta-analysis of randomised control trials

Abstract: Although TH appears to be safe in patients with STEMI, meta-analysis of published RCTs indicates that benefit is limited to reduction of infarct size in patients with anterior wall involvement with no demonstrable effect on all-cause mortality, recurrent myocardial infarction or HF/PO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 29 publications
2
33
0
6
Order By: Relevance
“…Compared to the 2.8‐Fr infusion catheter with side‐holes and OTW‐Balloon described by Otterspoor et al , the modified aspiration catheter used in our study had some excellent properties, including rapid catheter exchange, blockage of blood flow, easy crossover of the lesion, tip injection of the cold saline and thrombus aspiration as required. The mean door‐to‐flow restoration times in our hypothermia group were prolonged with 13 min ( P = 0.07), which was consistent with previous studies . Rapid induction of hypothermia in MaR with this cooling protocol was easily achieved without potential risk of induction of heart failure and pulmonary congestion.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Compared to the 2.8‐Fr infusion catheter with side‐holes and OTW‐Balloon described by Otterspoor et al , the modified aspiration catheter used in our study had some excellent properties, including rapid catheter exchange, blockage of blood flow, easy crossover of the lesion, tip injection of the cold saline and thrombus aspiration as required. The mean door‐to‐flow restoration times in our hypothermia group were prolonged with 13 min ( P = 0.07), which was consistent with previous studies . Rapid induction of hypothermia in MaR with this cooling protocol was easily achieved without potential risk of induction of heart failure and pulmonary congestion.…”
Section: Discussionsupporting
confidence: 90%
“…The recently pooled analysis of RCTs related to systemic hypothermia did not show a reduction in MACE, all‐cause mortality, heart failure, pulmonary edema and new myocardial infarctions . In this pilot study, we observed that clinical events including cardiac death, heart failure, reinfarction, TVR, cardiogenic shock, major bleeding, stroke, and repeat PCI did not differ between the groups at day 30 follow‐up.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Despite preliminary, since this minor result came from only four RCTs, the article by Villablanca and co-workers suggests that TH might be useful in a selected population with cardiac arrest or some subgroups of patients with STEMI. These results might be also explained by the fact that, differently from animal models of myocardial ischemia/reperfusion in which each 1 ℃ lowering of blood temperature cause a reduction in infarct size of 10% (17), the majority of STEMI patients in these RTCs did not reach the target temperature (12). These results were potentially influenced by the method to induce HT that was different in the RCTs [five RCTs used endovascular inferior vena cava (IVC) catheters and one a peritoneal catheter] (12).…”
Section: Post-ischemic Reperfusion Injury Is Mediated By Infiltrationmentioning
confidence: 99%
“…More recently, a systematic review and meta-analysis of randomized controlled trials (RCTs) investigated if TH might significantly reduce major adverse cardiovascular events (MACEs) as compared to controls in patients with STEMI. Villablanca and co-workers evaluated the clinical efficacy of this approach not only on MACEs (primary end point), but also on secondary end points, such as allcause mortality, new myocardial infarction, heart failure/ pulmonary oedema and infarct size (12). Finally, safety endpoints (i.e., all-bleeding, ventricular tachycardia and bradycardias) were also assessed.…”
Section: Post-ischemic Reperfusion Injury Is Mediated By Infiltrationmentioning
confidence: 99%